Indonesian Pencak Silat Tradition Models as The Intangible Cultural Heritage of Humanity - Suryo Ediyono; Reza Sukma Nugraha; Alif Al Hilal Ahmad (International Journal of Science and Applied Science: Conference Series, 2022)
Background of this research tradition Indonesian Pencak silat martial arts Intangible Cultural Heritage (ICH) certificate or an intangible cultural heritage certificate from the United Nations educational, scientific and cultural organization, or UNESCO. This research aims to find the cultural models of pencak silat as a martial art inherited from the ancestors of the Indonesian people to their children and grandchildren, which contain a lot of philosophy in them. Like the stance of the horses in pencak silat, they are rarely in a clenched fist, but always with their hands open. That means that pencak silat is not a form of self-defense to hurt people. But, aiming to defend yourself from the attacks of others. In the stance model of the horses, if someone invites a fight, they tend to avoid it. And if the opponent continues to attack, then the stance used is usually evasion. If the opponent is still attacking, then a defense is used. After being parried, it turns out that the opponent is still attacking, so we catch it and we paralyze it with a lock. That is, a fighter will never look for enemies. The stages of this research method use a historical-hermeneutic approach, descriptive qualitative with phenomenological methods. Javanology as a center of excellence for universities to develop Javanese ethics, Hamemayu hayuning bawono, and based on the value of local wisdom can show that the character of a warrior. Superior character is the process of cultural inheritance in the younger generation to form personality as a basis for perspective, think, behave and act. The targeted output of this research is the accredited national journal Sinta 2 Patanjala: Journal of Historical and Cultural Research, as well as reputable international journals indexed by Scopus Q1 Journal of Cultural Heritage.